2022
DOI: 10.1080/19336950.2022.2033511
|View full text |Cite
|
Sign up to set email alerts
|

A SWELL time to develop the molecular pharmacology of the volume-regulated anion channel (VRAC)

Abstract: Newly emerging roles of LRRC8 volume-regulated anion channels (VRAC) raise important questions about the therapeutic potential of VRAC in the treatment of epilepsy, type 2 diabetes, and other human diseases. A critical barrier to evaluating whether VRAC represents a viable drug target is the lack of potent and specific small-molecule inhibitors and activators of the channel. Here we review recent progress in developing the molecular pharmacology of VRAC made by screening a library of FDA-approved drugs for nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 81 publications
(66 reference statements)
0
16
0
Order By: Relevance
“… 55 Considering the possible off-target effects of DCPIB in enhancing M/Mφ phagocytosis and improving ICH prognosis, we always compared the results gained from DCPIB administration and Lrrc8a depletion, and found that they had similar effects on increasing M/Mφ phagocytosis, activating Nrf2/CD36 axis, and correcting neurobehaviors post-ICH. More specific blockers of the LRRC8A/VRAC 56 , 57 have been discovered, such as SN-401 58 and VI-116. 59 It is worth mentioning that DCPIB and other LRRC8A channel blockers may be administered to acute stroke patients in ambulances in the future, as these drugs are equally effective at improving the prognosis of hemorrhagic and ischemic strokes, possibly through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“… 55 Considering the possible off-target effects of DCPIB in enhancing M/Mφ phagocytosis and improving ICH prognosis, we always compared the results gained from DCPIB administration and Lrrc8a depletion, and found that they had similar effects on increasing M/Mφ phagocytosis, activating Nrf2/CD36 axis, and correcting neurobehaviors post-ICH. More specific blockers of the LRRC8A/VRAC 56 , 57 have been discovered, such as SN-401 58 and VI-116. 59 It is worth mentioning that DCPIB and other LRRC8A channel blockers may be administered to acute stroke patients in ambulances in the future, as these drugs are equally effective at improving the prognosis of hemorrhagic and ischemic strokes, possibly through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…5d, f, and 6b). Knowledge of the detailed filter architecture could be exploited in the design of potent and specific pore blockers binding to this region as strategy against diabetes and other VRAC-related diseases 37, 38 . An increased pore diameter can also be expected for heteromeric channels containing D and E subunits 13, 16, 17 , although it is currently unclear whether in a hexameric organization, this increase would be sufficiently large to account for the pronounced properties of these channels that renders them permeable also to larger substrates such as amino acids osmolytes and anti-cancer drugs 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Major breakthroughs have been made in recent years to characterize the structure and function of the PAC channel in biology and disease, but its regulation by endogenous molecules remains largely unexplored. PAC recently emerged as a target of interest for acidosis-related diseases, and much progress has been made to identify natural and synthetic compounds that can inhibit PAC channel ( Figueroa, 2020 ; Okada et al, 2021 ; Sato-Numata et al, 2016 ). DIDS (4,4-diisothiocyanatostilbene-2,2-disulfonic acid), a broad-spectrum chloride channel blocker, with a half-maximal inhibition (IC 50 ) of 2.9 µM in HEK293 cells ( Okada et al, 2021 ) is the most commonly used PAC inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…DIDS (4,4-diisothiocyanatostilbene-2,2-disulfonic acid), a broad-spectrum chloride channel blocker, with a half-maximal inhibition (IC 50 ) of 2.9 µM in HEK293 cells ( Okada et al, 2021 ) is the most commonly used PAC inhibitor. To date, arachidonic acid (IC 50 of 8.9 µM; Okada et al, 2021 ) and pregnenolone sulfate (IC 50 of 10 µM; Figueroa, 2020 ) are the only reported potential biological inhibitors of the acid-induced chloride currents ( I Cl,H ) mediated by PAC, yet their mechanism and binding sites are not fully characterized. Here, we show that PIP 2 potently inhibits PAC and present the first structure of PAC channel with an inhibitor.…”
Section: Introductionmentioning
confidence: 99%